2021
DOI: 10.1017/s003224742100005x
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic pack ice seal observations during spring across the Lazarev Sea

Abstract: The distribution, density and percentage contribution of pack ice seals during ship-board censuses in the marginal sea ice zone beyond the Lazarev Sea in spring 2019 are presented. Adult/juvenile crabeater seals (n = 19), leopard seals (n = 3) and Ross seals (n = 10) were sighted during 582.2 nm of censuses along the ship’s track line in the area bounded by 00°00’–22°E and 56°–60°S. Antarctic fur seals (n = 21) were only encountered on the outer fringes of the pack ice, and Weddell seals were absent due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…A two-week lactation duration is consistent with that of other pack ice seals, especially those that fast during the haul-out period (Robinson and Pomeroy, 2022). Similarly, the timing of this haul-out period at the end of October to early November corresponds with other studies observations of leopard seal adult-pup pairs and newborn pups during this time period (Brown, 1952;Joiris, 1991;Southwell et al, 2003;Acevedo et al, 2017;Bester et al, 2021).…”
Section: Joirissupporting
confidence: 86%
See 1 more Smart Citation
“…A two-week lactation duration is consistent with that of other pack ice seals, especially those that fast during the haul-out period (Robinson and Pomeroy, 2022). Similarly, the timing of this haul-out period at the end of October to early November corresponds with other studies observations of leopard seal adult-pup pairs and newborn pups during this time period (Brown, 1952;Joiris, 1991;Southwell et al, 2003;Acevedo et al, 2017;Bester et al, 2021).…”
Section: Joirissupporting
confidence: 86%
“…Lobodontines, like leopard seals, are considered ice-obligate breeders that travel to breeding habitats during the austral spring and early summer (Siniff, 1991;Southwell et al, 2003). Opportunistic observations of leopard seal adult-pup pairs have occurred from the beginning of October to the end of December, supporting an austral spring to summer breeding season for the species (Brown, 1952;Tikhomirov, 1975;Rogers et al, 1996;Southwell et al, 2003;Acevedo et al, 2017;Bester et al, 2021; , 1991). However, data on the exact timing and duration of breeding season are lacking.…”
Section: Movement Patternsmentioning
confidence: 99%
“…Furthermore, the deployment of biologging devices is limited to the spring and summer when the seals return to the pack ice to breed and moult very briefly; here, they prefer dense concentrations of interior pack ice (Condy 1977, Bester et al 2019), making it difficult to access them. However, advances in determining the distribution and abundances of Ross seals (Bengtson et al 2011, Southwell et al 2012, Gurarie et al 2017) and the identification of areas where Ross seals can predictably be found (Blix & Nordøy 2007, Bester et al 2020, 2021) invite further investigations. We suggest that an initiative for a coordinated, multinational, circumpolar, synchronous, comprehensive investigation into the ecology of the Ross seal is needed, especially in view of the United Nations Decade of Ocean Science and Sustainable Development (2021–2030; ).…”
Section: Discussionmentioning
confidence: 99%
“…We , 1960, -1990s (Joiris, 1991. In addition, circumstantial evidence suggests spring pack ice densities remain lower than before in the region (Bester et al, 2021). Thus, any future marine protection will likely require measures that take into consideration not only loss of habitat due to climate change, but also the loss of critical prey and changes in prey distribution that may ultimately impact foraging efficiency.…”
Section: Variable Importancementioning
confidence: 99%